2020
DOI: 10.1002/mp.14438
|View full text |Cite
|
Sign up to set email alerts
|

Couch and multileaf collimator tracking: A clinical feasibility study for pancreas and liver treatment

Abstract: Real-time tumor tracking through active correction by the multileaf collimator or treatment couch offers a promising strategy to mitigate delivery uncertainty due to intrafractional tumor motion. This study evaluated the performance of MLC and couch tracking using the prototype iTools Tracking system in TrueBeam Developer Mode and the application for abdominal cancer treatments. Methods: Experiments were carried out using a phantom with embedded Calypso transponders and a motion simulation platform. Geometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…62,63 It is thought that this 3D position estimation method can be adapted such that markerless 3D position and motion estimation is possible, either by using the location of the segmentation centroid or points on the segmentation outline instead of the marker locations. 64 An accurate estimation of the 3D position and motion of the tumor would allow for improved dose delivery through the use of beam adaptation methods 65 or gated treatments. 63 Currently for H&N cancer RT treatments, kV images are mainly acquired prior to treatment to assist in accurately positioning the patient.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 It is thought that this 3D position estimation method can be adapted such that markerless 3D position and motion estimation is possible, either by using the location of the segmentation centroid or points on the segmentation outline instead of the marker locations. 64 An accurate estimation of the 3D position and motion of the tumor would allow for improved dose delivery through the use of beam adaptation methods 65 or gated treatments. 63 Currently for H&N cancer RT treatments, kV images are mainly acquired prior to treatment to assist in accurately positioning the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration film of each case extended about 10–20% higher than the maximum dose of the case to anticipate the full dynamic dose range [ 2 ]. For EBT3, calibration was performed following our departmental procedure [ 15 ]. The calibration curve was generated with twelve points with a dose range from 0 cGy to 110% of the maximum dose of the clinical fields.…”
Section: Methodsmentioning
confidence: 99%
“…3. While good dosimetric accuracy has been reported [50,51], couch movement can cause unconscious physiological response. Still, Jöhl et al found acceptable levels of stress in healthy participants [52].…”
Section: Robotic Patient Positioningmentioning
confidence: 99%